A novel process for simultaneously improving the strength and plasticity of 18Ni(350) maraging steel - Feng Huang; Zhe Cheng; Daoling Zhang; Dongsheng Qian; Yanxiong Liu; Zhili Hu; Lin Hua (Journal of Materials Research and Technology)
A novel process involving cold deformation, cyclic solution, and two-step aging is developed for simultaneously improving the strength and plasticity of 18Ni(350) maraging steel. The strengthening and toughening mechanisms are elucidated by microstructural characterization and tensile property measurements. Cold deformation and cyclic solution refine the final martensite grains. In addition, two-step aging ensures the formation of numerous fine precipitates and a small amount of fine reversed austenite. Ultra-high strength is achieved by a combination of solid-solution, grain refinement, dislocation, and precipitation strengthening, with the latter having the largest contribution. Compared with the traditional process, the UTS and elongation are increased by 9.13% and 22.83%, respectively, to 2511 MPa and 5.81%, demonstrating the effectiveness of this novel process.